2016
DOI: 10.5194/acp-2016-979
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of fresh and aged organic aerosol emissions from meat charbroiling

Abstract: <p><strong>Abstract.</strong> Cooking emissions can be a significant source of fine particulate matter in urban areas. In this study the aerosol and gas phase emissions from meat charbroiling were characterized. Greek souvlakia with pork meat were cooked using a commercial charbroiler and a fraction of the emissions were introduced into a smog chamber where after a characterization phase they were exposed to UV illumination and oxidants. The particulate and gas phases … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…Figure 7 shows the evolution of O : C ratios and OS c of SOA from heated cooking oils as a O : C ratios and OS c of SOA from heated cooking oils as a function of OH exposure, together with the POA data. The O : C ratios and OS c of POA were in the range of 0.14 to 0.23 and −1.61 to −1.44, respectively, comparable to those of POA from meat charbroiling (Kaltsonoudis et al, 2016). As shown in Fig.…”
Section: Chemical Composition Of Soamentioning
confidence: 51%
See 2 more Smart Citations
“…Figure 7 shows the evolution of O : C ratios and OS c of SOA from heated cooking oils as a O : C ratios and OS c of SOA from heated cooking oils as a function of OH exposure, together with the POA data. The O : C ratios and OS c of POA were in the range of 0.14 to 0.23 and −1.61 to −1.44, respectively, comparable to those of POA from meat charbroiling (Kaltsonoudis et al, 2016). As shown in Fig.…”
Section: Chemical Composition Of Soamentioning
confidence: 51%
“…The mass spectra of cooking SOA also greatly resemble POA and field-derived COA in ambient air, with R 2 ranging from 0.74 to 0.88. Kaltsonoudis et al (2016) also observed that the ambient COA factor in two major Greek cities in spring and summer strongly resembled the aged SOA from meat charbroiling in a smog chamber.…”
Section: Soa Production Ratementioning
confidence: 79%
See 1 more Smart Citation
“…Finally, a series of gas monitors was used for the measurement of the mixing ratios of the nitrogen oxides (NO and NO 2 ), ozone (O 3 ), carbon monoxide (CO), and carbon dioxide (CO 2 ) (Teledyne models T201, 400E, 300E, and T360, respectively). Further online instrument descriptions and operating conditions are discussed in Kaltsonoudis et al ( 40 ).…”
Section: Methodsmentioning
confidence: 99%
“…The angle θ is a more sensitive metric for AMS mass spectra comparison that are often quite similar to each other. After the publication of Kostenidou et al (2009) the angle theta has been used in many other publications (e.g., Kaltsonoudis et al, 2017ACP, Florou et al, 2017ACP, Paciga et al, 2016, for AMS mass spectra comparisons. We have already stated in the Table 2 caption the reference of Kostenidou et al (2009) and that: "The angle θ provides a better comparison for small differences in the mass spectra (when R2 is less than 0.97)."…”
Section: Interactive Commentmentioning
confidence: 99%